Unravelling the Linguistic Veil: Leadership and the Position of Women from Al-Sya'rawi's Perspective - Rian, Rian Hidayat; Taufik Warman Mahfuzh; Akhmad Dasuki; Hanief Monady; Mahda (Medina-te : Jurnal Studi Islam, 2025)
The Position of Women in Leadership in Indonesia still faces various social and cultural challenges. Although the constitution guarantees women's right to lead, traditional social norms and gender stereotypes often become obstacles. This study aims to analyze Muhammad Mutawalli Al-Sya'rawi's views on leadership and the status of women in Islam through a linguistic approach. Al-Sya'rawi, an Egyptian exegete, is renowned for his linguistic-semantic method of interpretation, which offers a new perspective in understanding Qur'anic verses. This study uses a qualitative method to explore Al-Sya'rawi's perspectives on leadership and the role of women by analyzing his writings and understanding the cultural and social backgrounds that influenced his thought. An interpretative, descriptive, and content analysis approach is employed to examine Al-Sya'rawi’s interpretation of verses related to leadership and the status of women, particularly in Surah al-Nisā’ [4]: 34. The analysis shows that Islam provides equal opportunities for both men and women in the public sphere, while also emphasizing women's roles in the domestic sphere as wives and mothers, with rights and responsibilities equal to those of men. According to Al-Sya‘rawi, although women can participate in the public domain, leadership in general is still considered more suitable for men, given the significant responsibilities that leadership entails.